Penerapan Home Garden dalam Meningkatkan Ketahanan Pangan dan Solidaritas oleh Ibu Rumah Tangga di Desa Sibalanga - Susi Murni Lase; Elisamark Sitopu; Sudirman Lase; Elvri Teresia Simbolon; Ade Putera Arif Panjaitan (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2026)
This study aims to analyze the application of home gardens by housewives to improve food security and strengthen social solidarity in Sibalanga Village. The theoretical study uses the concepts of food security, empowerment theory, and Emile Durkheim's theory of social solidarity. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, in-depth interviews, and documentation, with key informants, housewives and the HePI Foundation. The results show that the application of home gardens can increase the availability, access, and diversity of family food, and reduce dependence on the market. In addition, this activity also strengthens social solidarity through the practice of mutual cooperation, sharing seeds, and harvests among residents. Assistance from the foundation also increases community knowledge and skills in yard management. In conclusion, home gardens not only function as a household-based food security strategy, but also as a means of empowerment and strengthening social relations in rural communities.